Využití dat z družice LANDSAT pro detekci tepelného znečištění v městské a příměstské krajině - Sedlák, Pavel; Prislingerb, Jan; Vysoudil, Miroslav (Univerzita Pardubice, 2010)
The aim of the paper is to show the way how satellite images can be used for detection of thermal pollution. Surrounding of Olomouc was study area. The influence of the urban heat island within this intensively agriculturally exploited area was examined. Images from LANDSAT were used. The images from two time periods were processed. The first image taken by the TM instrument dated back to October 1990. The second one is from the ETM+ instrument, October 2000. Kinetic temperature was calculated from both images. Finally, comparison of temperature from both two time horizons was done.
Keywords: remote sensing; LANDSAT; urban heat island